Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Total synthesis of (-)-radicamine B - Gurjar, Mukund K.; Borhade, Ramdas G.; Puranik, Vedavati G.; Ramana, C. V. (Tetrahedron Letters, 2006)
The synthesis of a chiral cyclic nitrone with L-arabino configuration and its application in the total synthesis of radicamine B is reported. An agreement in the spectral data with natural radicamine B but specific rotation with an opposite sign warranted a revision of the absolute configuration of radicamine B. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: codonopsinine; Cyclic nitrone; Grignard addition; polyhydroxy pyrrolidine alkaloids; radicamine B

Towards the total synthesis of clavosolide A - Yakambram, Pedduri; Puranik, Vedavati G.; Gurjar, Mukund K. (Tetrahedron Letters, 2006)
The synthesis of the monomeric unit of clavosolide A from 1,2:5,6-di-O-isopropylidene-alpha-D-glucose is presented. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: clavosolide A; diolide; reductive oxirane opening; seco acid; Simmons-Smith cyclopropanation

Tetranuclear manganese (III) salicylaldoxime ensemble - Kumbhar, Avinash S.; Mulay, Mahesh P.; Padhye, Subhash B.; Tavale, Sudam S.; Puranik, Vedavati G. (Structural Chemistry, 2008)
Crystal structure of {[Mn(salicylaldoximeH)(salicylaldoxime)](4)} center dot 3CHCl(3) 1 formed by the interaction of MnCl2 center dot 4H(2)O and salicylaldoxime in a 1:1 ratio is described. The compound crystallizes in the orthorhombic space group Pbca (No 61) with the lattice parameters; a = 27.769 (3), b = 22.672 (2), c = 21.650 (2) angstrom, V = 13630 (2) angstrom(3), Z = 8, R-1 = 0.0776, wR(2) = 0.2356, S = 1.164. The cluster with four Mn (III) centers formed by four terminal and four bridging salicylaldoxime ligands results in a central rotating wheel-like core with the Mn-Mn separation varying from 3.531 to 3.576 angstrom and with the diagonal distances being 4.156-4.165 angstrom. Four intramolecular H-bonds between a terminal oxime (NOH) group and the adjacent phenolate oxygen atom of another ligand stabilize the structure of the cluster. Spectral, magnetic, and cyclic voltammetry studies corroborate a stable Mn (III) tetramer.

Total synthesis of proposed auranthine - Kshirsagar, Umesh A.; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2010)
Starting from CBz-protected glutamic anhydride and Boc-protected o-aminobenzyl amine, the first total synthesis of proposed structure of auranthine has been reported. An intramolecular aza-Wittig reaction involving a lactam carbonyl group that delivered the diazepine core unit was the key step in the synthesis.

Total synthesis and structural revision of stagonolide D - Vadhadiya, Paresh M.; Puranik, Vedavati G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The total synthesis of the putative structure of stagonolide D has been completed. The relative and absolute configuration of stagonolide D was established by synthesizing its optical antipode. The adopted strategy involves the construction of the central macrolide employing ring-closing metathesis (RCM), followed by selective protecting group manipulations and a final concomitant −OTBS deprotection and displacement of an −OMs placed next to it, resulting in the formation of the epoxide ring.

Targeting a chemorefractory COLO205 (BRAF V600E) cell line using substituted benzo[alpha]phenoxazines - Pal, Sanjima; Konkimalla, V. Badireenath; Kathawate, Laxmi; Rao, Soniya S.; Gejji, Shridhar P.; Puranik, Vedavati G.; Weyhermueller, Thomas; Salunke-Gawali, Sunita (RSC Advances, 2015)
Mutational activations of the oncogene BRAF (especially BRAF V600E) result in a poor prognosis for colon cancer patients and are associated with chemoresistance rendering them refractory to treatment. The development of novel bioactive compounds with specific targeting abilities under such conditions is an urgent need in drug discovery. In this report we synthesize and characterize three fluorescent benzo[alpha]phenoxazine compounds (10R-benzo[alpha]phenoxazine-5-one, 1B; R = Cl, 2B; R = CH3, 3B; R = H) and their anticancer activities are evaluated in a COLO205 cell line. All three compounds with a log P value around 2 were cell permeable. However, 2B and 3B showed specific cytotoxicity in a malignant COLO205 cell line with a BRAF mutation (V600E) in comparison to a non-malignant wild-type BRAF HEK293T cell line. From further cell-based assays (cell cycle analysis, DNA fragmentation and caspase activation), we conclude that 2B and 3B treatment-induced selective cell death by inducing cell cycle arrest at the G0/G1 phase and caspase-mediated apoptosis (activation of the intrinsic and extrinsic pathways) are present only in BRAF V600E COLO205 cells. Further studies in the drug discovery pipeline might help develop these benzo[alpha]phenoxazines as promising chemotherapeutics for such refractory mutated cancers.